Mesoscopic transport in ferromagnetic oxides - Versluijs, Jan Johannes (Trinity College (Dublin, Ireland). School of Physics, 2002)
The study presented in this thesis is concerned with mesoscopic transport in half metallic ferromagnetic oxides. Two techniques have been developed to gain insight into the extrinsic transport properties of these oxides. The first, scanning tunneling potentiometry (STP), was used to correlate topographic features of a thin film sample with the flow of current through the sample. A Scanning Tunneling Microscope (STM) was modified succesfully to obtain simultaneously topographic and potentiometric images of a polycrystalline (Lao.7Sro,3) Mn03 thin film.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin